The computer vision workshop : develop the skills you need to use computer vision algorithms in your own artificial intelligence projects /: develop the skills you need to use computer vision algorithms in your own artificial intelligence projects. (2020) - Asad, Hafsa; Bhattacharya, Milon; Raghav, Aswin; Shrimali, Vishwesh Ravi; Singh, Nikhil
No abstract available